(untitled) (The Agriculturists, 2014)
A study was conducted to evaluate the effectiveness of three selected botanicals namely leaf extract of Neem (Azadirachta indica), Debdaru (Polyalthia longifolia) and datura (black) (Datura metel) along with Bavistin (Carbendazim) and BAU-biofungicide (Trichoderma harzianum) against leaf spot disease (tikka) of groundnut caused by Cercospora arachidicola and Cercosporidium personatum at the Field Research Farm of Bangladesh Agricultural University, Mymensingh during 2009-10. The most effective treatments were Bavistin, BAU-biofungicide (seed treatment + spray), BAU-biofungicide (spray) and leaf extract of Neem. Bavistin increased pod and dry haulm yield by 53.51 and 24-80 %, respectively. Maximum pod yield and dry haulm weight were recorded under Bavistin. BAU-biofungicide (seed treatment + spray) produced the second highest pod and dry haulm yield followed by leaf extract of Neem and BAU-biofungicide (spray). BAU-biofungicide (seed treatment + spray) and leaf extract of Neem may be recommended for controlling leaf spot disease of groundnut. DOI: http://dx.doi.org/10.3329/agric.v12i1.19579 The Agriculturists 2014; 12(1) 41-49